2023
DOI: 10.1002/ps.7600
|View full text |Cite
|
Sign up to set email alerts
|

Mealybug salivary microbes inhibit induced plant defenses

Abstract: BACKGROUNDPhenacoccus solenopsis is a polyphagous invasive mealybug that caused serious damage to crops worldwide. Phloem‐sucking hemipterans are known to carry symbiotic microbes in their saliva. However, the role of salivary bacteria of P. solenopsis in modulating plant defenses remains limited. Exploring the impact of salivary bacteria on plant defense responses will contribute to the development of new targets for efficient control of invasive mealybugs.RESULTSSalivary bacteria of the invasive mealybug P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…We recently found that Bacillus, Staphylococcus, Microbacterium, and Pseudomonas were colonized in P. solenopsis saliva . It is highly likely that these honeydew bacteria are derived from the salivary gland and gut of P.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently found that Bacillus, Staphylococcus, Microbacterium, and Pseudomonas were colonized in P. solenopsis saliva . It is highly likely that these honeydew bacteria are derived from the salivary gland and gut of P.…”
Section: Resultsmentioning
confidence: 99%
“…The universal primers 27F/ 1492R (27F: 5′-AGAGTTTGATCCTGGCTCAG-3′ and 1492R: 5′-GGTTACCTTGTTACGACTT-3′) were used to amplify 16S rRNA. The detailed procedure of 16S rRNA amplicon sequencing and the primers used have been described in our previous study 23 Attractiveness of Honeydew Bacteria to Fire Ants. To determine which isolated bacteria elicit the behavioral preference of fire ants, the behavioral response of fire ants to each identified bacterium was evaluated.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The S. symbiotica in pea aphids upregulated the effector in the salivary glands and suppressed the plant defences, which facilitated the colonization of aphids on host plants [39]. Similarly, symbiotic bacteria present in the mealybug (Phenacoccus solenopsis) saliva modulated phytohormone levels, thereby enhancing mealybug colonization on host plants [40]. Whether SCA endosymbionts utilize a similar or different mechanism(s) to manipulate host defences is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%